Evaluation of growth, puberty, osteoporosis, and the response to long‐term bisphosphonate therapy in four patients with osteoporosis‐pseudoglioma syndrome. Issue 7 (8th April 2022) - Karakilic‐Ozturan, Esin; Altunoglu, Umut; Ozturk, Ayse Pinar; Kardelen Al, Asli Derya; Yavas Abali, Zehra; Avci, Sahin; Wollnik, Bernd; Poyrazoglu, Sukran; Bas, Firdevs; Uyguner, Zehra Oya; Kayserili, Hülya; Darendeliler, Feyza
Abstract: Osteoporosis‐pseudoglioma syndrome (OPPG; MIM #259770) is a rare autosomal recessively inherited disease, characterized by early‐onset osteoporosis and congenital blindness, caused by loss‐of‐function mutations in the LRP5 gene. Beneficial effects of bisphosphonate treatment in patients with OPPG are well known, while follow‐up data on growth and pubertal parameters are limited. This article provides clinical follow‐up data and long‐term bisphosphonate treatment results in four OPPG patients from three unrelated families, ranging between 2.5 and 7 years of age at presentation. Clinical diagnosis was molecularly confirmed in all patients, with four different germline biallelic LRP5 mutations including a novel nonsense variant c.3517C>T (p.(Gln1173*)) in two siblings with marked phenotypic variability. Anthropometric and pubertal data and bone mineral density (BMD) measurements were evaluated retrospectively. Early puberty was observed in two patients. The bisphosphonate treatment duration of patients varied around 4–7 years and improvement in BMD z ‐scores with bisphosphonate treatment was demonstrated in all patients ( z ‐score changes were +5.6, +4.0, +1.0, and +1.3). Although further research is needed to identify the possible association between early puberty and OPPG, all OPPG patients should be followed up with detailed endocrinological evaluation regarding pubertal status.